Frozen Food Inventory Management System (FFIMS) for MS Nuri Global Resources / Noramiza Zakaria - Zakaria, Noramiza (2018)
Frozen Food Inventory Management System isan online inventory management system that study has been conducted at MS Nuri Global Resources company. Currently they are using manual process to manage their business activities with the agent and suppliers. The staff needsto manage the inventory and make an order to their supplier manually. Then, the staff will update the quantity and record it manually in a log book. While, agents have toorder manually and again the staff need t update the quantity manually. In order to solve the problem, Frozen Food Inventory Management System (FFIMS) has been proposed. Adapted waterfall model is used as a method to guide the whole process of the development of FFIMS. The adapted waterfallmodels involveplanning, analysis, design, implementation, testing and documentation. Besides that, system testing plan and evaluation from user and experts also has been done as a method to test the system capabilities, ease of use, usefulness, usability and interface design of the system. The system has been tested by three (3) expert users and thirty (30) respondents. The highest mean and standard deviation is ease of use with the mean 4.48 and standard deviation 0.57. As a conclusion this system will provide a better solution to manage the problem faced by MS Nuri Global Resources in managing their inventory. The system will help to make sure that there is no error in record keeping.